Digital natives and mobile advertising: Insights into consumer attitudes - Chong, Chin Wei; Teoh, Wendy Ming Yen; Lim, Shi Man; Hassan, Hasliza; Chaw, Lee Yen (Econjournals, 2025)
This study explores the attitudes of Malaysian digital natives toward mobile advertising, a crucial area given the increasing reliance on mobile devices for marketing. As digital natives—those who have grown up with technology—form a significant consumer base, understanding their perceptions is important for business engagement. Using a sample of 200 respondents, this study applies quantitative methods and employs SPSS for statistical analysis. The results confirm that information, entertainment, and credibility positively influence perceived value, while irritation has no significant impact. Furthermore, perceived value strongly influences attitudes of digital natives toward mobile advertising. These insights provide a framework for developing effective, consumer-friendly mobile advertising strategies. By analyzing these factors, the study seeks to identify patterns and preferences unique to Malaysian digital natives, providing a culturally relevant perspective. The findings will help develop targeted mobile advertising strategies that resonate with this tech-savvy audience, enhancing marketing effectiveness and consumer engagement in Malaysia’s rapidly evolving digital landscape. The study also aims to bridge the gap between academic research and practical application, offering actionable insights for marketers and advertisers operating in Malaysia.